A perfect bind - St. James, Dorothy (St. James, Dorothy. Beloved bookroom mysteries., 2022)
"Librarian Tru Beckett, ardent defender of the printed word, is about to find out that keeping murder checked out of her beloved library is much harder than she thought... Tru Beckett succeeded in building a secret book room in her now bookless library, where book lovers from lovely Cypress, South Carolina, can rejoice in the printed word. Now she's working hard to maintain the little library downstairs while keeping her "real job" upstairs in the bookless technology center. The last thing she needs is a mysterious vandal who seems intent on breaking into her secret book-filled sanctuary and creating chaos. The nasty interloper doesn't steal anything, but brutalizes the books, damaging them and knocking them off shelves. A patron of the secret book room tells Tru that there have been creepy goings-on at the library for years, especially in the basement where the secret book room is located. He's heard rumors of a poltergeist that haunts the library, determined to scare off readers. Tru is certain it's hogwash, but she's at a loss to think of who might be vandalizing the beautiful books she fought so hard to protect. And when a dead body shows up right behind the library, Tru is certain that it's not a ghost but a cold-blooded killer that she and her trusty tabby Dewey Decimal will need to uncover"--